Annual cycle of the microzooplankton communities in the waters surrounding the Palm Island Nature Reserve (north Lebanon), with special attention to tintinnids - ABBOUD-ABI SAAB, M. (Mediterranean Marine Science, 2002)
The distribution, abundance and annual cycle of microzooplankton communities have been studied monthly at five sampling stations in the north Lebanon, covering both neritic and oceanic waters in the vicinity of small islands situated 5 km offshore.In general, the density of microprotozoans, except for ciliates, increased from the coastal towards the offshore area, with stations situated near the islands being similar to the offshore rather than to the coastal ones. The microprotozoan species showed their highest numbers in late autumn and early winter. Foraminifera abundance ranged from 20 to 3390 inds.m -3 (mean= 549) whereas Acantharia abundance was highest in spring and ranged from 0 to 2608 inds.m -3 (mean 259). The Polycistina had their highest numbers in late winter, which ranged from 0 to 6024 inds.m -3 (mean= 740). The Heliozoa were abundant in late autumn with numbers ranging from 0 to 5165 inds.m -3 (mean= 555). The annual cycle of Tintinnids at all the stations was bimodal with a principal peak in October-November and another one in May, while minimum numbers were recorded in August-September. A succession of populations was observed all year round with a density ranging between 344 and 38986 inds.m -3 (mean = 10878). Ninety different species of Tintinnids were recorded. The diversity index varied between 0.19 and 4.15. It was concluded that there was a large-scale gradient in seasonal diversity which could be related to the annual average sea surface temperature and to the development of the vertical thermic structure.